Financial constraints and marital adjustments among married postgraduate students in Malaysia - Adewale, Abideen Adeyemi (2009)
Combining marital life with academic pursuit arguably seems a marriage of inconvenience. It is even more difficult when the students also need to work for their financial support. Nonetheless, it may offer no tenable grounds for non-pursuance of either; based on their seemingly mutual exclusivity. The concern for this study therefore, derives from the various adjustment issues that married students are faced with in their academic sojourn that may be due to their financial constraints. In this regards, data were elicited from the sampled postgraduate students of the Universiti Putra Malaysia (UPM) and International Islamic Universities (IIUM) to investigate the dimension of, and the relative impact of identified demographic factors especially their financial situation on their marital adjustments. Elicited by the need to fill an apparent quantitative research gap in this regards, particularly in a cosmopolitan institution as UPM and IIUM, the standard and hierarchical multiple regression was adopted in this study to capture various relationships among the latent and structural variables of interest. This was based on data collected via a survey questionnaire administered on sampled postgraduate respondents who met certain afore set criteria. Contingent upon the findings of the study, recommendations were offered.